Investigating the Association Between Exposure to Second Hand Smoke in utero and Developmental Coordination Disorder - Mahlberg, Nadilein; James, Maeghan E.; Bulten, Rheanna; Rodriguez, Christine; Kwan, Matthew; Cairney, John (Frontiers in Pediatrics, 2019)
Background: Developmental coordination disorder (DCD) and attention-deficit hyperactivity disorder (ADHD) are highly comorbid in children. There is evidence linking second hand smoke (SHS) exposure in utero to ADHD; however, it’s relation to DCD is unknown. The purpose of this study was to examine the effect of SHS exposure in utero in children with and without DCD. Methods: This study was a cross-sectional examination of 122 children from the District School Board of Niagara (72 males, 50 females, Mage=12.9 years) who were part of a larger, prospective cohort study. Participants were assessed for motor proficiency and intelligence and were screened for symptoms of ADHD using the Bruininks-Oseretsky Test of Motor Proficiency-Short Form, the Kaufman Brief Intelligence Inventory, 2nd edition, and the Conners’ Parent Rating Scales-Revised: Short Form, respectively. Parent questionnaires were used to determine SHS exposure in utero as either yes or no. Multinomial logistic regression was used to examine the relationship between SHS exposure and DCD risk. Results: Children exposed to SHS in utero were significantly more likely to be at high risk for DCD than children who were not (OR=3.33, p=0 .004), and children exposed to SHS in utero were more likely to be at moderate risk for DCD in the presence (OR=3.57, p=0.025) or absence of ADHD (OR=2.38, p=0.042). However, statistical adjustment for birth weight, socioeconomic status, age, and sex reduced this effect to non-significance in the moderate risk group. Conclusion: Results suggest exposure to SHS during pregnancy increases the chances of a child developing high risk DCD. While SHS exposure may increase DCD risk with and without ADHD, this effect may be explained by covariates and confounding factors. Further study is needed to examine the mechanisms linking SHS exposure in utero to motor coordination problems in children.